STUDENTS' PERCEPTIONS ON THE USE OF QUIZIZZ AS MEDIA FOR EVALUATION OF SOCIAL SCIENCE (IPS) DAILY ASSESSMENTS AT SMP NEGERI 9 MALANG - Eka Rahma Wati; Agung Wiradimadja (Jurnal PAJAR (Pendidikan dan Pengajaran), 2023)
Advances in information technology have a big positive impact to support educational advancement. One of them is Quizizz evaluation media. The research is based on the students' perceptions of the Quizizz evaluation media as an evaluation medium. It is aimed (1) to find out students' perceptions of whether applying Quizizz is able to reduce students' stress levels when carrying out daily assessments on social science learning subjects, and (2) to find out students' perceptions of the Quizizz's operation practicality as an evaluation medium. The research used a quantitative method and the data collection technique was questionnaires. The research respondents involved class VII students of SMP Negeri 9 Malang. The analytical method used was the frequency distribution analysis method. Thus, the following results indicate that (1) applying Quizizz could be a positive perception of 40.8% in a very good category in order to reduce student’s stress in carrying out daily assessments and (2) an average percentage of applying Quizizz was 29.6% in a pretty good category for operational practicality of media. Based on the research results, it is found that Quizizz was able to reduce students’ stress levels and was quite practical to use.